2014
DOI: 10.4236/aid.2014.44024
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Hantavirus in Central Iran as an Emerging Viral Disease

Abstract: Hantavirus is a zoonosis transmitted from rodents to humans. Asymptomatic infected rodents can secrete hantaviruses in the urine, feces, and saliva. The main route of infection transmission to human is aerosols contaminated with the virus. This study was designed to evaluate the serological and molecular prevalence of hantavirus as an emerging zoonoses disease among street sweepers in Isfahan province, central Iran. Serum samples from 200 street sweepers in healthy condition and those with recent renal failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In China, the Hantaan and Seoul viruses dominate HFRS infection, the leading rodent hosts of which are Apodemus agrarius and Rattus norvegicus, respectively [1,2]. The virus is transmitted from rodents to humans via inhalation of aerosols contaminated by rodents' urine, saliva, excreta, and dung, possibly through ingestion of contaminated food and by direct contact of contaminated materials with broken skin or mucous membranes, or by rodent bites [3,4]. Clinical HFRS manifestations include fever, headache, nausea, and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the Hantaan and Seoul viruses dominate HFRS infection, the leading rodent hosts of which are Apodemus agrarius and Rattus norvegicus, respectively [1,2]. The virus is transmitted from rodents to humans via inhalation of aerosols contaminated by rodents' urine, saliva, excreta, and dung, possibly through ingestion of contaminated food and by direct contact of contaminated materials with broken skin or mucous membranes, or by rodent bites [3,4]. Clinical HFRS manifestations include fever, headache, nausea, and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of Hantavirus circulation in Iran has been indicated in two earlier studies by Svedmyr et al and Chinikar et al Using indirect immunofluorescence assay, Svedmyr et al detected antibodies against Hantaan virus in human sera from Iran. In the other study, 200 sera from street sweepers in Isfahan province (central Iran) were tested by the same ELISA kits used in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…They found the IgM and IgG antibodies against Hantavirus in two and seven cases, respectively. Two sera were positive for RT‐PCR, but neither sequencing nor serotyping were conducted to determine the species of the virus . In contrast, in the present study, we utilized the EUROLINE Anti‐Hanta Virus Profile Global kits to further determine the Hantavirus species.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The major causative agents of HFRS in China are Hantaan orthohantavirus and Seoul orthohantavirus, which are associated with Apodemus agrarius and Rattus norvegicus as their hosts, respectively. It is reported that farmers, soldiers, and rural residents are at higher risk for hantaviruses because of the large population of rodent hosts in their surroundings and their sub-standard housing conditions [3,4]. Humans can be infected through virus contaminated aerosols, foods, or other materials and rodents bites [5,6].…”
Section: Introductionmentioning
confidence: 99%